MIR22HG Aggravates Oxygen-Glucose Deprivation and Reoxygenation-Induced Cardiomyocyte Injury through the miR-9-3p/SH2B3 Axis - Yi Ge; Lishi Liu; Liang Luo; Yu Fang; Tong Ni (Cardiovascular Therapeutics)
Reperfusion therapy, the standard treatment for acute myocardial infarction (MI), can trigger necrotic death of cardiomyocytes and provoke ischemia/reperfusion (I/R) injury. However, molecular mechanisms that regulate cardiomyocyte death remain largely unknown. The abnormal expression of lncRNA MIR22HG has been found in types of diseases. The current study was aimed at exploring the function and mechanism of MIR22HG in I/R injury. In this study, mouse myocardial cells (HL-1) treated with oxygen-glucose deprivation and reoxygenation (OGD/R) were used as the in vitro models, and myocardial ischemia reperfusion injury (MIRI) animal models in vivo were established in male C57BL/6 mice. Experiments including CCK-8, flow cytometry, TUNEL, HE staining, RT-qPCR, western blotting, and luciferase reporter assays were performed to explore the function and potential mechanism of MIR22HG in MIRI in vitro and in vivo. Bioinformatics analysis was performed to predict the binding site between miR-9-3p and MIR22HG (or SH2B3). Our results indicated that the MIR22HG level was upregulated in cardiomyocytes after OGD/R treatment. The knockdown of MIR22HG promoted cell viability and inhibited apoptosis and extracellular matrix (ECM) production in OGD/R-treated HL-1 cells. In mechanism, MIR22HG binds to miR-9-3p, and miR-9-3p targets the SH2B3 3′ untranslated region (UTR). Moreover, SH2B3 expression was positively regulated by MIR22HG but negatively modulated by miR-9-3p. Rescue assays suggested that the suppressive effect of MIR22HG knockdown on cell viability, apoptosis, and ECM accumulation was reversed by the overexpression of SH2B3. The in vivo experiments demonstrated that MIR22HG knockdown alleviated cardiomyocyte apoptosis and reduced myocardial infarct size in MIRI mice. In summary, MIR22HG knockdown alleviates myocardial injury through the miR-9-3p/SH2B3 axis.